Improving Students’ Critical Thinking through Problem-Based Learning in English Class at Grade XI SMK Swasta GKPI 1 Pematangsiantar - Heltri Firdayati S; Selviana Napitupulu (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the enhancement of students’ critical thinking performance through the implementation of Problem-Based Learning in an English class at Grade XI of SMK Swasta GKPI 1 Pematangsiantar. Employing a qualitative descriptive field research design, the study aims to examine how PBL facilitates the development of higher-order thinking skills within a vocational English learning context. Data were collected through classroom observations, interviews, document analysis, and critical thinking assessments conducted before and after the implementation of PBL. The findings indicate a significant improvement in students’ critical thinking performance across multiple indicators, including problem identification, logical reasoning, evaluation of ideas, decision-making, and reflective thinking. The results further reveal that PBL enhances students’ cognitive engagement by integrating authentic problem scenarios, collaborative inquiry, and reflective practices into English instruction. The vocational orientation of learning tasks strengthens relevance and supports deeper cognitive processing. This study contributes to the literature by providing empirical evidence on the effectiveness of PBL in vocational English education and highlights its potential to create student-centered, cognitively rich learning environments that support both language development and critical thinking growth